The Privacy of Mutual Consent in the Electronic Contract in the Algerian Legislation between General Rules and Special Legislation - Djebbar, Rekaia (جامعة قاصدي مرباح ورقلة - كلية الحقوق والعلوم السياسية, 2020)
The contract of sale via the internet is considered the most important contract on which electronic commerce depends, because it provides speed and ease in concluding transactions, where it is concluded without the need for the physical presence of the parties so there is no real contract board, but only virtual, so it falls within the range of contracts concluded, where the acceptance are exchanged via the Internet, it is immediate and contemporary, so studying this contract depends on understanding its concept, and focusing on the privacy of the consensual pillar by defining the concepts related to how the consensual existence and the convergence of acceptance in the contract that arises in the electronic environment, using the descriptive approach. And up to several results, including those related to the use of the data message to express the will in the electronic contract, the issue of the eligibility of the electronic contractor, the compatibility of the two wills in the electronic sales contract, and even with regard to the provisions of the electronic contract board, it has a kind of privacy.
يعد عقد البيع عبر شبكة الأنترنت أهم عقد تعتمد عليه التجارة الإلكترونية، لما يوفره من سرعة وسهولة في إبرام المعاملات، أين يتم إبرامه دون الحاجة إلى التواجد المادي للأطراف، أي عدم وجود مجلس عقد حقيقي بل افتراضي فقط، فهو بذلك يندرج ضمن طائفة العقود المبرمة عن بعد، حيث يتم تبادل الإيجاب والقبول عبر شبكة الإنترنت، فهو فوري ومعاصر، لذلك فإن دراسة هذا العقد يتوقف على إدراك مفهومه، والتركيز على خصوصية ركن التراضي بتحديد المفاهيم المرتبطة بكيفية وجود التراضي وتطابق الإيجاب والقبول في العقد الذي ينشأ في البيئة الإلكترونية، بانتهاج المنهج الوصفي. وصولا إلى عدة نتائج تميز عقد البيع الإلكتروني بخصوصية التراضي في عدة نواحي هي ما تعلق باستعمال رسالة البيانات للتعبير عن الإرادة في العقد الإلكتروني، ومسألة أهلية المتعاقد الإلكتروني، وتوافق الإرادتين في عقد البيع الإلكتروني، وحتى فيما يخص أحكام مجلس العقد الإلكتروني.
Keywords: العقود الإلكترونية -- عقد البيع الإلكتروني -- خصوصية التراضي -- القواعد العامة -- التشريعات الخاصة -- القانون الجزائري